Hydrilla of the UNIMAS Lakes: An Ash Glaze Composition - Shamsu Mohamad, (Wacana Seni Journal of Arts Discourse, 2005)
The presence of the fresh water aquatic weeds known as Hydrilla verticillata in the Universiti Malaysia Sarawak (UNIMAS) lakes drew the researcher to investigate their co,npositi on for possible use in ceramics. A 'quick and dirty experiment' soon followed and it was discovered that glaze characteristics are i ndeed evident in these aquatic weeds. They are glassy, not porous and have colors. This discovery led me to carry out further investigation on identifying the potential of tbe weeds for use in the ceramics industry.